Quantum measurement arrow of time and fluctuation relations for measuring spin of ultracold atoms - Maitreyi Jayaseelan (Nature Portfolio, 2021)
Irreversibility in quantum measurements shares conceptual links with statistical and thermodynamical irreversibility. Here, the authors are able to operationally associate an "arrow of time” to quantum weak measurements, testing it experimentally on a cloud of ultracold atoms.